Multifunctional Ti3C2Tx MXene Composite Hydrogels with Strain Sensitivity toward Absorption-Dominated Electromagnetic-Interference Shielding - Nicolosi, Valeria (My University, 2021)
The fast development of terahertz technologies demands high-performance electromagnetic interference (EMI) shielding materials to create safe electromagnetic environments. Despite tremendous breakthroughs in achieving superb shielding efficiency (SE), conventional shielding materials have high reflectivity and cannot be re-edited or recycled once formed, resulting in detrimental secondary electromagnetic pollution and poor adaptability. Herein, a hydrogel-type shielding material incorporating MXene and poly(acrylic acid) is fabricated through a biomineralization-inspired assembly route. The composite hydrogel exhibits excellent stretchability and recyclability, favorable shape adaptability and adhesiveness, and fast self-healing capability, demonstrating great application flexibility and reliability. More interestingly, the shielding performance of the hydrogel shows absorption-dominated feature due to the combination of the porous structure, moderate conductivity, and internal water-rich environment. High EMI SE of 45.3 dB and broad effective absorption bandwidth (0.2–2.0 THz) with excellent refection loss of 23.2 dB can be simultaneously achieved in an extremely thin hydrogel (0.13 mm). Furthermore, such hydrogel demonstrates sensitive deformation responses and can be used as an on-skin sensor. This work provides not only an alternative strategy for designing next-generation EMI shielding material but also a highly efficient and convenient method for fabricating MXene composite on macroscopic scales.
Keywords: MXene; Composite; Electromagnetic interference shielding; Multifunctional hydrogel; Terahertz absorption